Chinese Adolescents' Perceptions of Parental Socialization Goals: Variations by Ethnicity and Gender. (October 2022) - Zhang, Meng-Run; Ng, Florrie Fei-Yin
This research examined ethnic and gender variations in early adolescents' reports of parental socialization goals among the majority Han and two Muslim ethnic minority groups (Hui and Kazakhs) in China. 1584 adolescents (mean age = 13.49; 54.6% girls) listed and ranked the five most important goals from parents. Achievement outcomes were emphasized the most across ethnicities. According to adolescents, Han (vs. Kazakh) parents emphasized relatively more on self-maximization and psychological well-being, and less on extrafamilial relationships, morality, and social contribution, with the Hui appearing to be midway between the two groups. Gender differences in perceived parental goals were mostly consistent with traditional gender roles across ethnicities. This research painted a more nuanced picture of adolescents' perceptions of parental socialization in China. Results pointed to the significance of traditional values and economic development in understanding the socialization goals of Chinese parents of different ethnicities.